Quality of care for general medical conditions : a review of the literature and quality indicators - Kerr, Eve A. (Rand, 2000)
This report is one of five volumes providing detailed information on the QA Tools, RAND's comprehensive, clinically based system for assessing quality of care for children and adults. The QA Tools indicators encompass screening, diagnosis, treatment, and follow-up in 46 clinical areas and cover a variety of modes of providing care, including history, physical examination, laboratory study, medication, and other interventions and contacts. Development of each indicator was based on the ratings of a panel of experts in the relevant fields and on a focused review of the scientific literature, which is clearly documented for each clinical condition. This volume focuses on indicators for care of general medical conditions. Each chapter summarizes the results of the literature review for a particular condition, provides RAND staff's recommended indicators based on that review, and notes the level of scientific evidence supporting each indicator along with the relevant citations. In addition, this work details the process by which the expert panel evaluated the indicators and the final disposition of each indicator. Clinical conditions covered in this volume are: Acne, alcohol dependence, allergic rhinitis, benign prostatic hyperplasia, cataracts, cholelithiasis, dementia, depression, diabetes mellitus, hormone replacement therapy, headache, hip fracture, hysterectomy, inguinal hernia, acute low back pain, orthopedic conditions. Other RAND Health titles on the QA Tools system focus on indicators for children and adolescents, oncology and HIV, cardiopulmonary conditions, and women.